Prospective, Non-Controlled Pilot Study to Evaluate the Efficacy and Safety of Cefditoren Pivoxil in COVID-19 Patients with Mild to Moderate Pneumonia. Issue 1 (2022) - Leal, Cristóbal M. Rodríguez
No abstract available